Sequence and analysis of the complete mitochondrial genome of the Wuchuan Odorous Frog Odorrana wuchuanensis (Anura: Ranidae). Issue 1 (1st January 2016) - Huang, Yongjie; Zhao, Wei; Bao, Xinkang; Lin, Yinghua; Ran, Jingcheng
Abstract: The complete mitochondrial genome of the Wuchuan Odorous Frog was 18, 256 bp in length including 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region and was similar to that of typical vertebrates. The base composition was 27.89% A, 29.00% C, 15.34% G, and 27.78% T. All genes were encoded on the H-strand except ND6 and eight tRNA genes ( tRNAPro, tRNAGln, tRNAAla, tRNAAsn, tRNACys, tRNATyr, tRNASer, and tRNAGlu ), which were encoded on the L-strand. The phylogenetic relationship of Anura based on complete mitochondrial genomes showed that O. wuchuanesis is closest to O. margaretae with strong support and the genetic distance between Ranidae, Dicroglossidae, and Rhacophoridae was closer than others.